A reconsideration of multiple equilibria in the analysis of one-period government bonds with default risk - Yanling Guo (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
In this paper, the author considers sovereign debt in the form of one-period government bonds with default risk, which can be purchased by and traded among domestic and foreign investors. She shows that the "good equilibrium" is the only stable equilibrium under some quite general assumptions, while the "bad equilibrium" is an unstable one - a possible explanation for why the former is observed in practice. Given the "good equilibrium", the author further shows that the domestic debt share also determines the default risk: a higher domestic debt share means a lower default risk, ceteris paribus, which leads to a lower risk premium; while a lower domestic debt share means a higher default risk and a higher risk premium. Finally, she discusses some alternative interpretations of the domestic debt share.
Keywords: F34; H63; H74; H62; H6; H87; 330; public debt; sovereign debt; sovereign default; domestic debt; external debt; fiscal policy; government bond; government borrowing